Establishing a Framework for Healthy Community Design in Massachusetts. - Gorwood, Christine. (2017)
Abstract: Evolving evidence shows that changes need to be made to the built environment in the United States to reduce the health burden that has developed as a result of a lack of physical activity. The United States is experiencing a chronic disease crisis with the underlying cause for this epidemic being dramatic increases in the proportion of the population who are overweight, obese, or lacking in sufficient levels of physical activity. A directed search of the primary and secondary literature was conducted to identify the various guidelines and standards that have been developed to make recommendations for designing more healthful communities. These guidelines were reviewed and fifteen built environment design elements were selected by the author based on their relevance for the promotion of physical activity. The format of the Design Element documents was created to provide key information to relevant stakeholders during the various stages of the project design and planning processes. Evaluative feedback on the selected Design Elements was obtained via an on-line survey from professionals from various organizations working to promote physical activity within various organizations in Massachusetts. Most of the feedback was related to the following topics; adding information such as examples of existing projects to the Design Elements, refining the final set of Design Elements, and providing contextual background for users. Suggestions/recommendations were incorporated into the final Design Elements which will be used by the Pioneer Valley Planning Commission as part of a Healthy Community Design Toolkit being developed for use in Massachusetts to design more healthful communities.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Civil Engineering.; Advisor: David Gute.; Committee: Lea Susan Ojamaa.; Keywords: Environmental health, and Urban planning.